تأثيرات حجم البذرة ومحتوى التربة المائي في بزوغ بادرات صنفين من القمح القاسي ونموّها (Triticum turgidum var. Durum) - ديب, طارق; سوسي, فاتن (Latakia University Journal -Biological Sciences Series, 2019)
أجريت تجارب لقياس تأثيرات حجم البذرة، ومحتوى التربة المائي في بزوغ بادرات صنفين محسّنين من القمح القاسي ونموّها شام3 وشام1. تمّ انتخاب ثلاثة تدريجات لحجم البذرة بالنخل، وتمّ تحديد ثلاثة أدلّة تطوّرية ذات علاقة بالكتلة الحيوية لدى الصنفين وقياسها، عند مستويين رطوبيين للتربة (السعة الحقلية 39%، ونصف السعة الحقلية 20%). كان لتناقص المحتوى الرطوبي للتربة تأثيرٌ ضارٌّ في نسبة البزوغ، والمسطح الورقي للبادرة، وخاصةً معدّل ظهور الأوراق الأربع الأولى. وأثّر العجز المائي سلباً في كتلة البادرات الحية خلال مرحلة أربع الأوراق، وخاصّةً لدى الصنف شام1 بالمقارنة مع الصنف شام3. كانت صفة سطح البذرة من بين الصفات الشكلية الأكثر تأثراً بحجم البذرة. وارتبط حجم البذرة بقوّة بتطوّر البادرة وكتلتها الحيوية حتى النموّ الكامل لأوّل ورقتين. ويعدّ معدّل نموّ الورقة الأولى ومساحتها من أكثر الصفات المرتبطة بحجم البذرة. أنتجت البذرة الكبيرة بادرة أضخم، وتجلّى ذلك بوضوح تحت ظروف نقص الماء. وكانت الفروقات معنوية بين صنفيّ القمح القاسي شام1 وشام3، حيث كان معدّل نموّ الأوراق وتطوّرها أكبر في بادرات الصنف شام3 بالمقارنة مع الصنف شام1. كان الفعل المتبادل (طراز وراثي × حجم البذرة × محتوى رطوبي للتربة) معنوياً فقط في صفة الكتلة الحيوية للبادرة في مرحلة 4 أوراق. This work was conducted to evaluate the effects of seed size and soil moisture on emergence and seedling growth of two durum wheat cultivars, Sham3 and Sham1. Three different seed-grading sizes selected by sieving were used, and a set of three developmental and biomass-related indices was measured at two moisture levels: filed capacity (FC) 39%, and 50% of filed capacity 20%. The decrease of soil moisture from field capacity towards 50% of field capacity, affected emergence percentage, seedling leaf area, and mean rate of appearance of the first four leaves. Seedling biomass clearly affected by water stress, especially in Sham1. Seed area was the most morphological trait affected by seed size. Seed size was strongly associated with seedling development and seedling biomass until the complete extension of the first two leaves. The first leaf area and rate were the most characters associated with seed size. Large seed produced large seedling, particularly under water stress conditions. Significant differences were found between the two varieties, where leaf growth rate and development were higher in Sham3 than Sham1. The interaction effect (cultivars × seed size × soil moisture) was significant just for seedling biomass trait at the fourth leaf stage.